இறையனார் அகப்பொருள் இறுதி நூற்பா - இடைச்செருகலா? / Is Iraiyanaar Agaporul's Final Stanza an Interpolation? - முனைவர் பா. ஜெய்கணேஷ் / Dr. B. Jaiganesh (International Journal of Tamil Language and Literary Studies, 2023)
The ancient grammar text Tolkappiyam paved the way for many new grammar texts in detail in later periods. Chapters on Love brought new texts such as “Iraiyanaar Agapporul”, and “Nambiyakapporul”, chapter on war brought Puraththinai Iyal, chapters on poetics brought texts like Yaapparungalam and Yapparungala kaarikai etc. Regarding love life, Iraiyanar has written in the book “Iraiyanaar Agapporul”. This is not a primary text, it is a secondary text following “Tolkappiyam”. This secondary text relates religion and the Pandiya Kingdom as a reason for its new arrival. The commentary for the book gives vivid explanations for all the Stanzas. The commentator was skilled enough to give life to the book for centuries through his exemplary comments for the original text. There are 60 Sutras in “Iraiyanaar Agaporul”, as indicated by the book published for the first time in 1883 by Dr. C.V. Damodaram Pillai. Literary historians and researchers who studied it later documented the same. In 1916 Bavaanandam Pillai published the same text and he mentioned the last definition i.e. the 60th was not found in the original manuscript or palm script. Professor A. Damodaran who published the same text in 2013 after scrutinizing all the palm scripts confirmed that the 60th sutra and definition were not found in any scripts. Then how this 60th stanza (Noorpa) and definition was included in the text? To find a solution to this problem, this article tries to discuss the facts related to it and the discussions based on it.